Frequency and Density Associated Grouping Patterns of Male Roosevelt Elk - Weckerly, Floyd W. (Frontiers in Ecology and Evolution, 2020)
Group size variation has been examined within a framework of costs and benefits to ecological factors. Social factors might also influence group size particularly in polygynous males. To explore the role of social and ecological factors on group size outside the mating season I examined the influence of abundance on male grouping patterns in a population of Roosevelt elk (Cervus elaphus roosevelti) in northwestern California, USA. Male grouping patterns are complex, males often group with other males, but they can be transient members of female groups. Because male–male competition is pervasive even outside of the mating season, male only groups display fusion–fission dynamics which should be coupled to abundance of the male population. Whereas the number of males in female groups is governed by female abundance. Males associating with females is more likely at low female abundance because per capita forage should be abundant. Across a 23-year study I examined whether male or female abundance was related to male only group sizes and the number of males in female groups. Male only group size displayed a positive, linear relationship (frequency associated) with male abundance and the number of males in female groups displayed an inverse, positive relationship (density associated) with female abundance. The female population varied in K carrying capacity which influenced relationships with number of males in female groups. Uncovering factors influencing male grouping patterns required using the appropriate metric of abundance. Social factors influenced male only group sizes and ecological factors influenced male prevalence in female groups.